2022
DOI: 10.1111/vde.13109
|View full text |Cite
|
Sign up to set email alerts
|

Noncompartmental pharmacokinetics of three intravenous mycophenolate mofetil concentrations in healthy Standardbred mares

Abstract: Background: Mycophenolate mofetil (MMF) is the prodrug of mycophenolic acid (MPA) which acts as an immunosuppressive agent. During the biotransformation of MMF to MPA, additional metabolites including MPA phenol glucuronide (MPAG), MPA acyl glucuronide (AcMPAG) and MPA phenol glucoside (MPG) are formed. Objective: To define the noncompartmental pharmacokinetic (PK) parameters of three single doses of intravenous (i.v.) MMF and its downstream metabolites in healthy horses. Animals: Six healthy Standardbred mare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 37 publications
(95 reference statements)
1
10
0
Order By: Relevance
“…In a previous study, escalating IV doses of 1, 5, and 10 mg/kg yielded MPA AUCs lower than reported therapeutic plasma concentrations in humans, with the 10 mg/kg dose achieving the highest plasma MPA AUC concentration. All doses were tolerated well by every horse 11 . With limited information on drug metabolism, accumulation, and tolerability in horses, we avoided doses higher than 10 mg/kg for this multiple‐dose study with the aim of preventing drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, escalating IV doses of 1, 5, and 10 mg/kg yielded MPA AUCs lower than reported therapeutic plasma concentrations in humans, with the 10 mg/kg dose achieving the highest plasma MPA AUC concentration. All doses were tolerated well by every horse 11 . With limited information on drug metabolism, accumulation, and tolerability in horses, we avoided doses higher than 10 mg/kg for this multiple‐dose study with the aim of preventing drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Lower limits of quantification for MMF, MPA, MPAG, AcMPAG, and MPG were 0.043, 0.32, 0.993, 0.993, and 0.483 ng/mL, respectively. The bioanalytical LC‐MS/MS assay was fully validated according to the Food and Drug Administration (FDA) Bioanalytical Method Validation Guidance as described previously 11 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations